Ultrasound measurement of the transverse diameter of the fetal thymus in pregnancies complicated by the preterm prelabor rupture of membranes - Musilova, Ivana; Hornychova, Helena; Kostal, Milan; Jacobsson, Bo; Kacerovsky, Marian (Journal of clinical ultrasound, 2013)
PURPOSE: To determine whether the measurement of the transverse diameter of the fetal thymus is of value in the identification of either histologic chorioamnionitis or funisitis in pregnancies complicated by preterm prelabor rupture of membranes (PPROM). METHODS: The transverse diameter of the fetal thymus was measured in 216 fetuses from PPROM pregnancies. A small thymus was defined as a transverse thymic diameter below the fifth percentile according to a previously published nomogram. The placenta, the fetal membranes, and the umbilical cord were assessed for the presence of inflammation. RESULTS: A small thymus was identified in 69% (150/216) of fetuses. A small thymus was present in 80% (106/133) and 88% (36/41) of women with histologic chorioamnionitis or funisitis, respectively. The presence of a small thymus had a sensitivity of 79%, specificity of 47%, positive predictive value of 71%, negative predictive value of 59% for the identification of chorioamnionitis (p < 0.0001; odds ratio 3.5) and a sensitivity of 88%, specificity of 35%, positive predictive value of 24%, and negative predictive value of 92% in the identification of funisitis (p = 0.004; odds ratio 4.4). CONCLUSIONS: The sonographic finding of a small thymus is a sensitive indicator of histologic chorioamnionitis or funisitis; low specificity excludes it as a possible clinical implication in the management of PPROM pregnancies.
Keywords: Fetal Membranes, Premature Rupture; těhotenství; Predictive Value of Tests; Gestational Age; Sensitivity and Specificity; prediktivní hodnota testů; Adult; gestační stáří; ultrasonografie; ženské pohlaví; Humans; Pregnancy; Thymus Gland; předčasný odtok plodové vody; senzitivita a specificita; Ultrasonography; chorioamnionitida; dospělí; Chorioamnionitis; thymus; Female; lidé